Kualitas Hidup Generasi Z Di Tengah Kemajuan Teknologi - Tia Ristika Sari (Yayasan Darussalam Bengkulu, 2024)
This research aims to analyze how technological advances affect the quality of life of generation Z. In an increasingly sophisticated digital era, generation Z is a group that is very dependent on technology, both in aspects of education, communication, entertainment and work. This research uses a qualitative approach with a literature study method. Data was collected from various scientific articles, books, journals and research reports related to the topic of quality of life for Generation Z and the influence of technology. The research results show that technology has a positive impact in facilitating access to information and employment opportunities, but also increases risks related to mental health and technology dependence. This article concludes that technology has an ambivalent influence on the quality of life of generation Z, depending on its usage patterns.